PRINSIP KESANTUNAN BERBAHASA PERANGKAT KANTOR DESA AIR LIMAU KECAMATAN MUNTOK KABUPATEN BANGKA BARAT - Anggraini, Riska; Wahidy, Achmad; Heru, Agus (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2023)
The purpose of this study was to identify and describe the principles of politeness in the language of the Air Limau Village Office, Muntok District, West Bangka Regency. The data source of this research is the Air Limau village office apparatus selected as research informants with a total of 4 village officials. Speech taken by village apparatus utterances with people who have needs at the Village office. The method used in this research is descriptive qualitative method and the data technique is observation technique, SLC observation technique (see competently involved) SBLC (listen free to speak competently), recording technique, and note taking technique. Keywords: politeness, spoken language, village office apparatus